THE ROLE OF THE SILK ROAD IN GLOBAL CIVILIZATION - Qodirov Mirzaolim (Ustozlar uchun, 2025)
Abstract. The Silk Road was more than a network of trade routes—it was a conduit for cultural, religious, scientific, and technological exchange between the East and West. This article explores the historical development of the Silk Road, its socio-economic and political impact, and its legacy in shaping global civilization. Emphasis is placed on the roles of key empires, innovations, and the intercultural dialogue that flourished along these ancient routes.